Decision-making on A Novel Stochastic Space-I of Solutions for Fuzzy Volterra-Type Non-linear Dynamical Economic Models - Alsaedy, Anas Faiz; Alshabhi, Salah H.; Mohammed, Mustafa M.; Khalid, Thwiba A.; Mustafa, Arafa O.; Bashir, Runda A. A.; Taha, Nidal E.; Bakery, Awad A. (Contemporary Mathematics, 2024)
In this paper, we explain the sufficient conditions on a novel constructed stochastic space by weighted generalized Gamma matrix and variable exponent sequence spaces of fuzzy functions, for the Kannan contraction operator to have a unique fixed point. Finally, we discuss the numerous applications of solutions to Fuzzy Volterra-Type Non-linear Dynamical Economic Models and illustrate them with some examples.